(3fXQjI JMdjdjI bjGSjIs - (3eMeO Vja Gddg(B, (3GdbWGHQjs ((3YeGf(B:s (3OGQ ZjOGA(B,s, 2011)
(3GdfXQjGJ h GdSjGSGJ GdfbOjI h gjcd h eDTQGJ COGA GdGbJUGO Gdjefj , fTCI h JWhQ GdLgGR GdeUQaj h GdeGdj h GdSjGSGJ GdfbOjI h GdGSJbQGQ GdGbJUGOj, GdSjGSGJ GdfbOjI h GdJfejI GdGbJUGOjI h GdJMdjd GdbjGSj dOhQ GdSjGSI GdfbOjI aj GdGSJbQGQ h GdJfejIs
(3eQGLY U(B.399s
Keywords: (3GdEbJUGOs; (3GdJfejIs; (3GdJfejI GdGLJeGYjI h GdGbJUGOjI ` Gdjefs; (3GdSjGSI GdfbOjIs